APA Handbook of Giftedness and Talent. 2018
DOI: 10.1037/0000038-026
|View full text |Cite
|
Sign up to set email alerts
|

Developing talents in girls and young women.

Abstract: When gifted programs are not available, early admittance to kindergarten may be the best option for challenging gifted girls. Many school districts resist this, however, where delaying kindergarten, especially for boys, is considered an acceptable way of ensuring larger size and social maturity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
0
7
0
1
Order By: Relevance
“…Research has indicated females with culturally traditional work-family ideologies are more likely to have lower career aspirations regardless of their own abilities (Davis & Pearce, 2007;Lirio et al, 2007). Researchers point out that girls are often raised in families, schools, and communities that have different career expectations of boys than of girls (Kerr, 1994;Kronborg, 2010;Reis, 1998;Rimm et al, 1999). Girls may be unaware of the impact these expectations have on their choices.…”
Section: Career Development Considerations For Gifted Girlsmentioning
confidence: 99%
“…Research has indicated females with culturally traditional work-family ideologies are more likely to have lower career aspirations regardless of their own abilities (Davis & Pearce, 2007;Lirio et al, 2007). Researchers point out that girls are often raised in families, schools, and communities that have different career expectations of boys than of girls (Kerr, 1994;Kronborg, 2010;Reis, 1998;Rimm et al, 1999). Girls may be unaware of the impact these expectations have on their choices.…”
Section: Career Development Considerations For Gifted Girlsmentioning
confidence: 99%
“…Όσον αφορά στις διαφορές μεταξύ των δύο φύλων, φαίνεται ότι τα χαρισματικά αγόρια επιτυγχάνουν υψηλότερους επαγγελματικούς στόχους από ότι τα χαρισματικά κορίτσια (Eccles, 1985. Kerr & Gahm, 2018.…”
Section: η τελειοθηρία και η διαχείρισή τηςunclassified
“…This situation justifies the regular school -in the role of its principals, teachers and other educational agents, in addition to the community -to take the initiative to provide conditions to identify the talented / gifted student in order to offer him/her the necessary assistance. (Hill, Corbett, & Rose, 2010;Kerr & Gahm, 2018).…”
Section: Introductionmentioning
confidence: 99%